2007
DOI: 10.2134/agronj2006.0166
|View full text |Cite
|
Sign up to set email alerts
|

Production and Nutritive Value of Grazed Simple and Complex Forage Mixtures

Abstract: Sustainability of forage production in the Northeast USA is affected by environmental and climatic variability. Complex forage mixtures may be better adapted than simple mixtures to variable environments and produce greater dry matter (DM) yield more evenly throughout the growing season, thereby increasing sustainability of forage production. A grazing trial was set up to evaluate forage production, nutritive value, and botanical composition dynamics of well-adapted and commonly sown forage species. The forage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
3
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 21 publications
9
82
3
9
Order By: Relevance
“…As the digestibility of organic matter (IVOMD) and NDF in grass were higher than in the forbs and legumes [16], IVOMD and NDF decreased when more forbs and legume species were included (Fig 5). Previous studies have shown that differences in nutritive value appear to be more closely related to differences in the relative proportions of the functional groups than to mixture complexity [16, 44]. We also found that the 10-mix and the 12-mix had similar nutritive value, while the 3-mix with a larger proportion of grass had the highest concentrations of IVOMD and NDF.…”
Section: Discussionsupporting
confidence: 68%
“…As the digestibility of organic matter (IVOMD) and NDF in grass were higher than in the forbs and legumes [16], IVOMD and NDF decreased when more forbs and legume species were included (Fig 5). Previous studies have shown that differences in nutritive value appear to be more closely related to differences in the relative proportions of the functional groups than to mixture complexity [16, 44]. We also found that the 10-mix and the 12-mix had similar nutritive value, while the 3-mix with a larger proportion of grass had the highest concentrations of IVOMD and NDF.…”
Section: Discussionsupporting
confidence: 68%
“…Low clover growth rate, especially for white clover, affected initial harvests possibly due to its low competitive ability for light and low stolon density during its establishment [23]. In binary mixtures, white clover establishment is affected by grass density and maturity, a reduced sward density and early maturity would probably increase compatibility [24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…is one of the most common grass species in the humid transition zone between the temperate North and mild South in the eastern half of the USA [5]. It was also one of the most dominant species in complex mixtures with other grasses and legumes at the end of a grazing study in Pennsylvania [6]. Maintaining adequate legumes in tall fescue was related to improved animal performance and farm profitability [7].…”
Section: Introductionmentioning
confidence: 99%